2022
DOI: 10.3390/jpm12081320
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth and Neonatal Outcomes in Pregestational Diabetes Mellitus in a Population with a High Prevalence of Diabetes

Abstract: The aim of this retrospective study, conducted in an Italian tertiary care hospital, was to evaluate maternal-fetal and neonatal clinical outcomes in a group of patients with pregestational diabetes mellitus (PGDM), such as diabetes mellitus type 1 (DM1), diabetes mellitus type 2 (DM2), and maturity onset diabetes of the young (MODY). Overall, 174 pregnant women, nulliparous and multiparous, with a single pregnancy were enrolled. Data on pregnancy, childbirth, and newborns were collected from medical records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In this study, macrosomia was the most common neonatal finding related to GDM, which is supported by studies showing that GDM is associated with macrosomia [25,27]. Moreover, RDS was strongly associated with all types of maternal DM, which is supported by studies showing that GDM and pre-GDM had a greater association with RDS [26,[28][29][30], and Sepsis was related to maternal diabetes, which is also supported by a study that showed greater concern between sepsis and maternal DM and hypertension [31]. In this research, association between maternal diabetes and neonatal death was found, which is supported by previous studies that had suggested an association with neonatal mortality [32] but is different from a study that showed no association between maternal diabetes and neonatal necrotizing enterocolitis, intraventricular hemorrhage, or neonatal death [33].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, macrosomia was the most common neonatal finding related to GDM, which is supported by studies showing that GDM is associated with macrosomia [25,27]. Moreover, RDS was strongly associated with all types of maternal DM, which is supported by studies showing that GDM and pre-GDM had a greater association with RDS [26,[28][29][30], and Sepsis was related to maternal diabetes, which is also supported by a study that showed greater concern between sepsis and maternal DM and hypertension [31]. In this research, association between maternal diabetes and neonatal death was found, which is supported by previous studies that had suggested an association with neonatal mortality [32] but is different from a study that showed no association between maternal diabetes and neonatal necrotizing enterocolitis, intraventricular hemorrhage, or neonatal death [33].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, macrosomia was the second most common neonatal finding related to GDM, which is supported by studies showing that GDM is associated with macrosomia [25,27]. Moreover, RDS was strongly associated with all types of maternal DM, which is supported by studies showing that GDM and pre-GDM has a greater association with RDS [26,[28][29][30], and Sepsis is related to maternal diabetes, which is also supported by a study that showed a stronger relationship between sepsis and maternal DM and hypertension [31]. In this research, an association between maternal diabetes and neonatal death was found, which is supported by previous studies that suggested an association with neonatal mortality [32], but is different from a study that showed no association between maternal diabetes and neonatal necrotizing enterocolitis, intraventricular hemorrhage, or neonatal death [33].…”
Section: Discussionsupporting
confidence: 82%
“…Pre-existing DM primarily refers to type 1 or 2 DM diagnosed before pregnancy, which complicates one to two percent of all pregnancies and accounts for 13 to 21 percent of DM cases in pregnancy [3,4]. This condition substantially threatens maternal and perinatal outcomes, including miscarriage, congenital anomalies, preterm birth, preeclampsia, and increased perinatal morbidity and mortality [5][6][7]. An increase in hemoglobin A1c (HbA1c) levels from 5.6 to 6.8 % can triple the risk of congenital abnormalities [8,9].…”
Section: Introductionmentioning
confidence: 99%